Mapping of Research on Knee Osteoarthritis to Analyse the Trends and Collaborations: Bibliometric and Content Analysis - Sulfandy, Sulfandy; Azliyana Azizan; Zarina Zahari (Journal of Liaquat University of Medical & Health Sciences, 2025)
This study employed bibliometric and text analysis techniques to identify collaboration patterns, trends, and key themes in research related to knee osteoarthritis. The keywords used in this study were "knee osteoarthritis", "pain", and "management". Two main databases were used, namely Scopus and WoS. The literature search obtained 191 (56.80%) articles from Scopus and 145 (43.20%) articles from WoS related to the given keywords. Duplicate analysis was carried out, and 123 duplicates were obtained from the combination of the two databases. After that, the data collected consisted of 213 articles, with details from 143 (67.10%) articles in WoS and 70 (32.90%) in Scopus. The dataset identifies Indonesia and Malaysia as the primary contributors, with 93 and 121 publications, respectively. Other countries, such as China, India, the Netherlands, Thailand, and Pakistan, also participated in the collaborative effort. Key Malaysian institutions driving this research include the University of Malaya, Universiti Sains Malaysia, Universiti Kebangsaan Malaysia, Universiti Teknologi Malaysia, International Islamic University Malaysia, Sunway University, and the University of Kuala Lumpur. In Indonesia, the University of Indonesia stands out with 17 publications, accompanied by Universitas Gadjah Mada. In conclusion, both Malaysia and Indonesia have established themselves as key players in the field of knee osteoarthritis research, demonstrating their commitment to advancing scientific knowledge and fostering international collaboration.